Simulation training improves team dynamics and performance in a low-resource cardiac intensive care unit - Sivaram Subaya Emani; Catherine K Allan; Tess Forster; Anna C Fisk; Christine Lagrasta; Bistra Zheleva; Peter Weinstock; Ravi R Thiagarajan (Wolters Kluwer Medknow Publications, 2018)
Introduction: Although simulation training has been utilized quite extensively in highincome medical environments, its feasibility and effect on team performance in lowresource pediatric Cardiac Intensive Care Unit (CICU) environments has not been demonstrated. We hypothesized that lowfidelity simulationbased crisis resource management training would lead to improvements in team performance in such settings. Methods: In this prospective observational study, the effect of simulation on team dynamics and performance was assessed in 23 healthcare providers in a pediatric CICU in Southeast Asia. A 5day training program was utilized consisting of various didactic sessions and simulation training exercises. Improvements in team dynamics were assessed using participant questionnaires, expert evaluations, and video analysis of time to intervention and frequency of closedloop communication. Results: In subjective questionnaires, participants noted significant (P < 0.05) improvement in team dynamics and performance over the training period. Video analysis revealed a decrease in time to intervention and significant (P < 0.05) increase in frequency of closedloop communication because of simulation training. Conclusions: This study demonstrates the feasibility and effectiveness of simulationbased training in improving team dynamics and performance in lowresource pediatric CICU environments, indicating its potential role in eliminating communication barriers in these settings.